2021
DOI: 10.11646/zootaxa.4999.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Who’s your daddy? On the identity and distribution of the paternal hybrid ancestor of the parthenogenetic gecko Lepidodactylus lugubris (Reptilia: Squamata: Gekkonidae)

Abstract: The widespread parthenogenetic gecko Lepidodactylus lugubris is comprised of several clonal lineages, at least one of which has been known for some time to have originated from hybridization between its maternal ancestor, Lepidodactylus moestus, and a putatively undescribed paternal ancestor previously known only from remote islands in the Central Pacific. By integrating new genetic sequences from multiple studies on Lepidodactylus and incorporating new genetic sequences from previously sampled populations, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…We are also aware of some recognised taxa that show very limited morphological or genetic divergence from other taxa, and may be synonyms (e.g., Lepidodactylus browni and Lepidodactylus orientalis or Lepidodactylus pantai and Lepidodactylus woodfordi ; PMO pers. obs., Karin et al 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…We are also aware of some recognised taxa that show very limited morphological or genetic divergence from other taxa, and may be synonyms (e.g., Lepidodactylus browni and Lepidodactylus orientalis or Lepidodactylus pantai and Lepidodactylus woodfordi ; PMO pers. obs., Karin et al 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The mourning gecko, Lepidodactylus lugubris (Duméril and Bibron, 1836), is a species of small gecko, native to Central Pacific islands but currently introduced to many tropical areas around the world (e.g., Karin et al, 2021). It belongs to the species‐rich genus Lepidodactylus (Uetz et al, 2022) which in turn belongs to the Gekkonidae and is closely related to Gekko , Luperosaurus and Pseudogekko (Gamble et al, 2012; Wood et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…It belongs to the species‐rich genus Lepidodactylus (Uetz et al, 2022) which in turn belongs to the Gekkonidae and is closely related to Gekko , Luperosaurus and Pseudogekko (Gamble et al, 2012; Wood et al, 2020). It is a parthenogenetic, all‐female species, consisting of several clonal lineages, probably originating from a hybridogenetic event between L. moestus and L. pantai (Karin et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…No previous study has investigated the factors that might influence interspecific differences in the dispersal ability of island squamates in the Pacific Ocean, although similar research in the Mediterranean showed important variability among species depending on certain morphological traits (Escoriza, 2021). These differences may be related to spatial (arrangement of the archipelagos) and ecological (island invasibility) factors, and the life‐history traits of the colonizing species, but also to human‐mediated dispersal (Jordal et al., 2001; Karin et al., 2021; Sanchez & Probst, 2014).…”
Section: Introductionmentioning
confidence: 99%